Villages where China's ethnic minorities live - Björn Gustafsson; Ding Sai (Institute for the Study of Labor (IZA), 2006)
This paper investigates how ethnic minorities in rural China are faring compared with the ethnic majority. The village is the unit of analysis and large surveys for 2002 are used. Minority villages in northeast China are found to have a somewhat better economic situation than the average majority village, but minority villages in the southwest are clearly faring worse. Industrialisation, inputs in agricultural production, stock of human capital of the labour force, wage level on the local labour market as well as indicators of path dependency are all found to affect the economic situation of a village. Location is the single most important circumstance working against a favourable economic situation for minority villages in the north- and particularly the southwest. Low village income results in long-distance migration for many ethnic minorities, but for some minorities their ethnicity hinders migration.
urn:nbn:de:101:1-20090309100
Keywords: 330; Ethnische Gruppe; Dorf; Regionale Disparität; Soziale Lage; China